Assessment of the influence of force account in achieving value for money in construction projects in Tanzania: A case of Bariadi Town Council - Mayani, Stephen (Mzumbe University, 2024)
A Dissertation Submitted in Partial/Fulfillment of the Requirements for Award of the Degree of Master of Science in Procurement and Supply Chain Management (MSc. PSCM) of Mzumbe University, 2019